8 - Book Reviews: G. Aforka NWERE: Harmonization of African Foreign Policies, 1955 1975: the political economy of African diplomacy (Boston: Boston Univer sity African Studies Center, 1980. African Research Studies Number 14) x, 285 pp. / 10. - SHAW, Timothy M. (Africa Development, 1980)
Timothy M. SHAW, Dalhousie University, Nova Scotia, Canada.